2020
DOI: 10.3390/ijerph17072298
|View full text |Cite
|
Sign up to set email alerts
|

Stalking and Intrusive Behaviors in Ghana: Perceptions and Victimization Experiences

Abstract: Most studies of stalking and other forms of intrusive behavior are conducted in the West. Little is known about the phenomenon in the African context. The present work represents the first dedicated stalking study conducted in Ghana. Based on a sample of 371 male and female university students, this study explored the gender distribution of overall perceptions and experiences, and frequency and duration of personal worst experiences of stalking and intrusive behavior. Several significant gender differences wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…There are various definitions of stalking, from a narrow legal definition that requires the stalker to demonstrate intent and the victim to feel fear, to broader definitions that encompass lists of constituent behaviors (see [ 4 ]). Although most of the research on stalking has been conducted in Australia, the U.S., and the U.K., an increasing number of studies conducted in under-researched populations (e.g., Denmark, Finland, Germany, Ghana, Hong Kong, Lithuania, mainland China, the Netherlands, Portugal, South Africa, Singapore, and Spain) have found stalking to be a common, and perhaps universal, problem [ 5 , 6 , 7 , 8 , 9 ]. The traditional view of stalking is that the perpetrators of stalking are more likely to be male, whereas the victims are more likely to be female [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are various definitions of stalking, from a narrow legal definition that requires the stalker to demonstrate intent and the victim to feel fear, to broader definitions that encompass lists of constituent behaviors (see [ 4 ]). Although most of the research on stalking has been conducted in Australia, the U.S., and the U.K., an increasing number of studies conducted in under-researched populations (e.g., Denmark, Finland, Germany, Ghana, Hong Kong, Lithuania, mainland China, the Netherlands, Portugal, South Africa, Singapore, and Spain) have found stalking to be a common, and perhaps universal, problem [ 5 , 6 , 7 , 8 , 9 ]. The traditional view of stalking is that the perpetrators of stalking are more likely to be male, whereas the victims are more likely to be female [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The modified version of the “Stalking: International perceptions and prevalence” questionnaire (SIPPQ) developed by Sheridan et al [ 41 ] was used in this study. The original and modified versions of the measures (consisting of 42 and 47 stalking and intrusive behaviors, respectively) were adopted in at least 10 other studies [ 13 , 14 , 16 ], with samples recruited in 14 countries (Armenia, Australia, Egypt, England, Finland, Ghana, India, Indonesia, Italy, Japan, Portugal, Scotland, Singapore, and Trinidad). The samples collected were from a mix of community and university students, but none were regarded as representative of the wider population.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, recent research has consistently demonstrated that stalking and intrusive incidents are not unusual and possibly occur in every country [ 12 , 13 , 14 ]. An increasing number of empirical studies conducted with samples from under-researched populations in recent years (e.g., Denmark, Finland, Germany, Ghana, Hong Kong, Lithuania, mainland China, the Netherlands, Portugal, South Africa, Singapore, and Spain) found that the prevalence rates of stalking and intrusive incidents to range from 5% to 55% [ 7 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations